A comparative study of efficacy and safety of glucosamine plus chondroitin sulphate versus rosehip as add on therapy to NSAIDs in patients suffering from osteoarthritis - Kaur, Kiranpreet; Kaur, Anjleen; Singh, Prabhsimran; Bakshi, Amandeep Singh (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Osteoarthritis is a chronic and debilitating disease. Management of disease is a big challenge. NSAIDS play an important role but have many adverse reactions. So, this study was designed to evaluate the efficacy and safety of natural compound rosehip versus glucosamine and chondroitin sulphate in patients of osteoarthritis. Methods: An open label, randomized, parallel group comparative study, conducted on patients of either sex with confirmed diagnosis of osteoarthritis on standard NSAIDs therapy, attending the outpatient department of orthopedics in a tertiary care centre. 150 patients were enrolled and divided into three groups (group A, group B and group C) of 50 each. Patients of group A were given Glucosamine plus chondroitin sulphate for 12 weeks. Group B was given rosehip for 12 weeks and group C placebo. These supplements were given as add on therapy. Patients were monitored and adverse drug reactions were noted. The data was analysed statistically using t- test for efficacy and descriptive stats for assessing the safety. Results: Efficacy was assessed by comparing mean reduction in the pain intensity between group A and B, group B gives highly significant results as compared to group A. While comparing joint tenderness, swelling around joint, mean functional capacity and improvement in the overall assessment, group B gives significant results as compared to group A. It was also observed that group A and group B were better than group C in all the efficacy parameters. All the drugs were well tolerated and systemically safe. Conclusions: There was significant difference in efficacy of rosehip compared with glaucosamine and chondroitin sulphate in patients of osteoarthritis. In comparison there was no significant difference in safety of two drugs and both were considered safe in patients.